Violencia física y su influencia en las relaciones sociales durante la etapa del noviazgo, en una pareja de adolescentes de 15-17 años - Garcia Espinoza, Andrea Carolina (2019)
This case study is about physical violence and its influence on social relationships during the dating period, in a couple of teenagers between 15 and 17 years old, who have been dragging a life path full of both family and social problems. On the part of the aggressor, he is in his experiences since a violent family child, which reflects with his partner to cause permanent conflicts in their relationship. This research project exposes the identification of different types of violence and the effects it causes in the most vulnerable, highlighting the physical violence from the psychological area that is being developed and analyzed from different perspectives, both of the aggressor and the victim, in the dynamics of social influences of a particular case